2018
DOI: 10.1017/s0265051717000286
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Student Learning and Leadership through a University-Community Choral Initiative

Abstract: Within a rapidly changing higher education landscape, there is an increased need for universities to look beyond their ‘ivory towers’ and into their surrounding communities in preparing students for the ‘real world’. Findings from an Irish case study explore a children's choral university-community initiative within an urban area of socio-economic disadvantage. The choral initiative involved 14 student volunteers and 150 children. Qualitative research, carried out over two years, involved student focus group i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 29 publications
(65 reference statements)
0
12
0
1
Order By: Relevance
“…They are thrilled to do this in the group. (RL,workshop 2) Fatima singles herself out here as the "other" amongst a choir of 150 children, despite the choir being quite racially and socially diverse (see Kenny, 2018;Kenny, Bourke, & Ní Chonduín, 2016). The asylum seeker identification as "one from Knockalisheen" is thus most striking as is the relief and joy at not being as alone in this association as originally perceived.…”
Section: Identitymentioning
confidence: 99%
“…They are thrilled to do this in the group. (RL,workshop 2) Fatima singles herself out here as the "other" amongst a choir of 150 children, despite the choir being quite racially and socially diverse (see Kenny, 2018;Kenny, Bourke, & Ní Chonduín, 2016). The asylum seeker identification as "one from Knockalisheen" is thus most striking as is the relief and joy at not being as alone in this association as originally perceived.…”
Section: Identitymentioning
confidence: 99%
“…Preservice music educators (PMEs) have reported that authentic teaching experiences in primary and secondary schools helped prepare them for a career in music education (Teachout, 1997; Conway, 2002; Kenny, 2018) and had lasting positive impacts on their development as teachers (Conway, 2012; Bartolome, 2017). When examining seventh-, eighth- and ninth-grade (aged 12–14 years) band students’ perceptions of an authentic teaching experience with PMEs, Kruse (2012) found that students perceived the experience as generally positive, but they also reported challenges such as ‘instructional clarity and low affect’ (p. 68).…”
Section: Introductionmentioning
confidence: 99%
“…In music education, researchers have found that PMEs benefited from service-learning experiences (Reynolds & Conway, 2003; Burton & Reynolds, 2009; Bartolome, 2013). For example, PMEs have reported that service-learning experiences improved their ability to: (a) provide student-centred instruction (Sindberg, 2020), (b) build relationships and connect with primary students aged 9–12 years (Kenny, 2018), and (c) identify personal biases and engage with students from cultures and demographics with which they were unfamiliar (Forrester, 2019). Therefore, service-learning experiences might foster the development of teacher/student rapport that are difficult to engender through in-class lectures or peer-teaching exercises (Forrester, 2019; Sindberg, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…This comprehensive international volume, edited by Catherina Christophersen and Ailbhe Kenny (2018), is essential reading for musicians, teachers and researchers who are working, or wish to work, collaboratively in educational settings.…”
mentioning
confidence: 99%
“…As Bresler notes in the opening, this is a burgeoning area of research. Indeed, collaborative practice forms the backdrop in several recent BJME articles (inter alia Viig, 2019;Rodríguez-Sánchez, Odena, & Cabedo-Mas, 2018;Kenny, 2018;Baker, Bull, & Taylor, 2018). This timely volume is divided into three sections: Critical Insights, Crossing Boundaries and Working Towards Partnership, each with an emphasis on theoretical frameworks, challenges around such initiatives and empirical studies, respectively.…”
mentioning
confidence: 99%